A bidirectional association between smartphone addiction and depression among college students: A cross-lagged panel model - Zhang, Kexin; Guo, Haiyun; Wang, Tianli; Zhang, Jianghui; Yuan, Guojing; Ren, Juan; Zhang, Xueqing; Yang, Huayu; Lu, Xiaoyan; Zhu, Zhihui; Du, Jun; Shi, Haiyan; et al. (Frontiers in Public Health, 2023)
Background Smartphone addiction (SA) is associated with adverse consequences, especially for freshmen. Evidence indicates that SA is associated with depression, and it is necessary to conduct a longitudinal study to explore the association further. Methods SA (measured by the Smartphone Addiction Scale-Short Version) and depression (measured by the Zung’s Self-Rating Depression Scale) among 1,186 freshmen were surveyed at baseline and a respective 12-month follow-up for each participant. The application of a cross-lagged panel model approach (CLPM) revealed an association between SA and depression after adjusting for demographic variables. Results The CLPM results showed a significant path from baseline SA to follow-up depression (β=0.08, P<0.001) and a significant path from baseline depression to follow-up SA (β=0.08, P<0.001). Compared with the overall cross-lagged model, the cross-lagged coefficient of the path from baseline SA to follow-up depression increased in the female group (β=0.10, P=0.015), and the cross-lagged coefficient of the path from baseline depression to follow-up SA also increased significantly (β=0.15, P<0.001). In contrast, the cross-lagged model in the male group showed no predictive effect between SA and depression (P>0.05). Conclusions The current study showed a significant bidirectional association between smartphone addiction and depression among freshmen, but only in the female population.